ANALYSIS OF OBSTACLES FACED BY POLICE INVESTIGATIONS IN RESOLVING CASES OF CRIMINAL ASSAULT THROUGH RESTORATIVE JUSTICE AT THE INVESTIGATION STAGE - Yogandono, Satoto (Universitas Labuhanbatu, 2025)
This research explores the challenges faced by police investigators in resolving cases of assault through Restorative Justice (RJ) during the investigation phase. The objective is to identify and analyze the obstacles encountered by investigators when implementing RJ in the context of assault cases. The study employs a normative juridical method with a qualitative approach, focusing on legal norms outlined in regulations and the living norms in society. Data collection was conducted through library research, reviewing literature, legal documents, and previous studies. The findings reveal several key obstacles: legal factors, including unclear or conflicting regulations; the quality and understanding of law enforcement personnel; insufficient facilities and resources; societal resistance to RJ, favoring traditional punitive measures; and cultural factors where retributive justice is still prevalent. To overcome these challenges, the study recommends enhancing resources, increasing public awareness, and improving cultural attitudes towards RJ. This approach aims to ensure that RJ is more effectively implemented, achieving a more comprehensive and accepted form of justice. Keywords: Restorative Justice, Police Investigators, Assault Crimes